An 8 Years' experience in surgical treatment of anal fistula - Gulmez, Selcuk (Annals of Medical Research, 2021)
Aim: To review our experience with patients who had been operated for perianal fistula based on cryptoglandular etiological basis and to reveal risk factors affecting postoperative results.Material and Methods: A total of 65 perianal fistula patients, who underwent surgical treatment, were screened for this retrospective study.Results: The mean age was 45.4 ± 10.6 years, with a predominance rate of male patients. The previous surgery rate for anal sepsis was 44.6%. The median (min-max) follow up time was 19 (15–103) weeks, and the duration of symptoms was 18 (6-250) weeks. The most common fistula type was intersphincteric (36.9%), and fistulotomy was the most preferred surgery (50.8%). New postoperative incontinence was found in 6 (8.2%) of patients, 5 (83.3%) of them had gas incontinence. The healing rate in the follow-up period was unsatisfactory for 12 (18.5%) patients. The significant risk factors for failure were BMI≥30 kg/m2 (p0.001), complex fistula with multiple fistula tracts (p=0.001), duration of symptoms ≥12wk (p=0.012), a history of previous surgery for anal sepsis (p=0.001), the presence of baseline incontinence (p=0.003), procedures except for fistulotomy (p=0.009).Conclusion: The risk factors most associated with failure were obesity (BMI≥30 kg/m2) and multiple fistula tracts. Other significant risk factors leading to failure were duration of symptoms ≥12wk, a history of previous surgery for anal sepsis, the presence of baseline incontinence, complex fistula type, and non-fistulotomy procedures. This study suggests the need for comparative, randomized controlled studies that investigate methods and their outcomes, particularly in complex fistulas.
Keywords: Fistulotomy, LIFT, perianal fistula